-2(6n-8)=16-12n

Simple and best practice solution for -2(6n-8)=16-12n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6n-8)=16-12n equation:


Simplifying
-2(6n + -8) = 16 + -12n

Reorder the terms:
-2(-8 + 6n) = 16 + -12n
(-8 * -2 + 6n * -2) = 16 + -12n
(16 + -12n) = 16 + -12n

Add '-16' to each side of the equation.
16 + -16 + -12n = 16 + -16 + -12n

Combine like terms: 16 + -16 = 0
0 + -12n = 16 + -16 + -12n
-12n = 16 + -16 + -12n

Combine like terms: 16 + -16 = 0
-12n = 0 + -12n
-12n = -12n

Add '12n' to each side of the equation.
-12n + 12n = -12n + 12n

Combine like terms: -12n + 12n = 0
0 = -12n + 12n

Combine like terms: -12n + 12n = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4k+7=-4 | | 7K+-8K+-5K= | | 8x-2=-9+nx | | x-.55x=0 | | 1=-15+8x | | 12=1.5 | | 2(3x-5)=9-(2x-5) | | 0.2x-6=x | | 2(5d+3)=4d | | -5.6+12.2=5h | | 4(m-3)=-32 | | 4x+6x+1=0 | | x^2-5=sqrt(3*x) | | -23-2p=19-p | | 12x^2+35x-3=0 | | 7=9(2f+5) | | 3(2x+3)=4-x | | 4w-7=3w+1 | | x^2+18x+30=0 | | 4x-5=4x-9 | | 1/2n+5/6=2/3 | | (6x+2)+20=90 | | -8-7x-6x=-8 | | 18=a(a-7) | | 4x=14x-30 | | 6b+15=4b+19 | | -84=-7(x+5) | | (6x+2)+20=360 | | 20+.5= | | bing=-2 | | -20=-4x+-6x | | -5.6+12.2=5 |

Equations solver categories